FIGO good practice recommendations on reduction of preterm birth in pregnancies conceived by assisted reproductive technologies. Issue 1 (14th September 2021) - Mol, Ben W.; Jacobsson, Bo; Grobman, William A.; Moley, Kelle; ,
Abstract: FIGO (the International Federation of Gynecology and Obstetrics) supports assisted reproductive technologies (ART) to achieve pregnancy and supports their availability in all nations. However, the increased frequency of preterm birth must be taken into account. Therefore, before in vitro fertilization (IVF) is started, other approaches, including expectant management, should be considered. Single embryo transfer is the best approach to ensure a live, healthy child. However, increased risks for preterm birth are also associated with a singleton IVF pregnancy and should be discussed and contrasted with spontaneous conception. Increased preterm birth and other adverse pregnancy outcomes in singleton IVF cycles warrant investigations to elucidate and mitigate. Minimizing embryo manipulation during cell culture is recommended. Increased risk of preterm birth and other pregnancy complications in ART could reflect the underlying reasons for infertility. This information should be discussed and further explored. Synopsis: Assisted reproductive technologies to achieve pregnancy should be globally available. In in vitro fertilization cycles, single embryo transfer is the best approach to ensure a healthy live child.